"Going forward" the changing facet of partnership base business structure; development of venture capital vehicles in Malaysia - Abd Ghadas, Zuhairah Ariff (2011)
Partnerships structure has long been accepted as one of the major venture capital vehicles. It is generally opted by small and medium businesses and by the professionals who are not allowed by their respective regulatory bodies to incorporate. With the development of the economy, the general partnership structure was found to be no longer suitable for some of the businesses, particularly the professionals. The rising cost in trade and litigation has forced partners to take precaution as regards to liabilities in the business. These lead to development in partnerships structure to limited partnerships (LP) and limited liability partnerships (LLP). In the United States of America (USA), the partnership structure has undergone a more rapid evolution to include master limited partnership and family limited partnership. In Singapore, LP and LLP had also been introduced. In Malaysia, the Companies Commission of Malaysia (CCM) had published two consultation documents on Limited Liability Partnerships (LLP); in 2003 and 2008 respectively. The discussion draft bill for LLP has also been released to few professional regulatory bodies in April 2009. The CCM initiatives marked a major step of development in Malaysian business laws after 54 years after independence but yet setting with only three-business structure. In Labuan, the Malaysian offshore, the Labuan Limited and Limited Liability Partnerships Act 2010 allows both LP and LLP to be registered in Labuan. This paper shall discuss the new venture capital vehicle in Malaysia, namely LP and LLP which are based upon partnership structure. The main objective of this paper is to highlight the changes on legal attributes of the partnership structure in its due course of evolution; with special reference to the legal status and liability regime.